Consumer engagement with self-expressive brands : brand love and WOM outcomes : an extension of wallace, buil and chernatony (2014) applied to Instagram in Portugal - Mendes, Pedro Filipe Magalhães Bessa (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence